Tafsīr Al-Aḥkām's Analysis of Demoralization in Cases of Sexual Harassment in Educational Institutions in Indonesia - Sangaji, Ruslan; Amin, Surahman; Muhammadun, Muzdalifah; Syarifuddin, Samsinar; Usman, Bustami (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
Sexual harassment is a violation of Islamic law and is inconsistent with the values of all religions and moral norms. The rise of sexual violence in educational institutions is concerning. This study aims to analyze and evaluate the demoralization that occurs in Indonesian educational institutions after the emergence of sexual harassment committed by caregivers or staff. Using a descriptive qualitative method analyzed through the tafsīr al-aḥkām approach, data was collected through interviews and literature studies. The findings indicate that sexual harassment in educational institutions is often done through coercion, using dogmatic methods or luring victims. This behavior undermines the maqāshid of the Qur'an, teachings of all religions, and moral norms. Teachers and caregivers are meant to be dignified and honorable people. Sexual harassment is a form of sexual violence that harms victims both physically and mentally. Interpretation scholars emphasize that every individual has the right to dignity and honor, which Islamic shari'a regulates. Therefore, Islamic law prohibits immoral acts, including sexual harassment, which is considered faḥsyā’ or fāḥisyah (abominable), as it can injure human glory and dignity. The demoralization that occurs will affect the degradation of the charisma of educational institutions and weaken the sacred relationship between caregivers and students.